Redescription of Parapercis okamurai Kamohara, 1960 (Perciformes: Pinguipedidae), based on specimens newly collected from Taiwan and Japan - Ho, Hsuan-Ching (Zootaxa, 2014)
A rare species of sandperch, Parapercis okamurai, is redescribed based on 2 types and 15 specimens newly collected from Taiwan and Japan. The species is unique in having cycloid scales on the parietal, opercle and subopercle, except for few large ctenoid scale that covers the base of the opercular spine; body color yellowish dorsally, with 10 or 11 faint yellow bands on lateral body and pale ventrally; and black spots on inner side of upper pectoral fin base. It can also be distinguished from congeners by having a combination of the following characters: dorsal-fin rays V, 23; anal-fin rays I, 19; pectoral-fin rays 18; pored lateral-line scales 59–64; medial predorsal scales 9–10; transverse scale rows 4.5–5.5/14–15; circumpeduncular scales 20–21; gill raker4–5+9–10=13–16; -4 pairs of canine teeth at front of lower jaw; 2–4 rows of teeth on vomer; 2 rows of teeth on palatines; scales on cheek moderately large, each half embedded; and body color yellowish dorsally and a prominent ocellus at upper caudal-fin base.